(untitled) (Indian Journal of Animal Production and Management, 2024)
Azolla pinnata is a good source of protein and has a high feeding value as it contains almost all essential amino acids, major minerals such as calcium, phosphorus, magnesium, sodium, potassium; trace minerals including iron, copper, zinc, cobalt apart from substantial amount of vitamin A precursor beta carotene and vitamin B12. The current experiment was conducted to study the nutritive value in Azolla pinnata that can be used as a feed supplement. Azolla was cultivated in pits, harvested every week, and shade dried. The proximate analysis was done for the sample of shade dried azolla. It contained 84.95 percent organic matter, 23.74 percent crude protein, 4.09 percent ether extract, 14.25 percent crude fibre, 34.96 percent nitrogen free extract, 15.05 percent total ash, 1.69 percent calcium and 0.54 percent phosphorus.